Diversidad de especies forestales de la familia Euphorbiaceae del Blowndow de la Reserva Nacional Alpahuayo Mishana, kilometro 28 carretera Iquitos Nauta Loreto Perú. 2021 - Manihuari Murayari, Cesar Gonzalo (2022)
The present research work was carried out in the Alpahuayo-Mishana National Reserve located at Km 28 of the Iquitos-Nauta highway, within the framework of the project "Taxonomy of Forest Species in the Experimental Areas of the UNAP", Agreement signed between the Ministry of Education (MINEDU) and the National University of the Peruvian Amazon (UNAP) No. 021-2020, called Research Project: "Taxonomy of Forest species of the experimental area of UNAP. In order to carry out the taxonomic identification of forest species with DAP ? 10cm belonging to the Euphorbiaceae family. 137 individuals distributed in 10 genera and 19 species belonging to the Euphorbiaceae family have been identified; the genus Mabea has 5 species followed by Conceveiba and Hevea with 3 species, the IVI was determined, expressed as a percentage, noting that the highest IVI is the forest species Micrandra spruceana 18.505% Of the total, followed by Nealchornea yapurensis Huber with 17,981 and with Senefeldera skutchiana Croizat 11.324%.